Decreased Incidence of Intraventricular Hemorrhage in Extremely Low Birth Weight Infants Using Customized Circulatory Management to Evaluate the Hemodynamic Change of Patent Ductus Arteriosus - Huang, Wan-Heng; Li, De-Ming; Hsu, Chung-Ting; Lin, Yi-Hsuan; Hsu, Ya-Chi; Wang, Teh-Ming; Lin, Ming-Chih (Frontiers in Pediatrics, 2021)
Background: In extremely low birth weight (ELBW) infants, the patent ductus arteriosus (PDA) with left-to-right shunt and an increase in systemic artery resistance may cause increasing preload and afterload of the left ventricle. The immature myocardium in ELBW infants has a limited ability to respond to the change, which leads to hemorrhagic complications. In this study, we detected the hemodynamic change of cardiac performance and applied a clinical strategy to prevent PDA-associated hemorrhagic complications in ELBW infants. Methods: We enrolled ELBW infants at a single medical center in Taiwan. The customized circulatory management was performed by echocardiography after birth until the PDA closed. Inotropic agents were administrated according to the requirements of hemodynamic parameters or clinical conditions. The primary outcomes were hemorrhagic complications including pulmonary hemorrhage and intraventricular hemorrhage (IVH) greater than grade II. The secondary outcomes were the rate of surgical ligation of PDA, mortality, necrotizing enterocolitis, and bronchopulmonary dysplasia. Results: A total of 20 ELBW infants were evaluated by customized circulatory management from 2019 to 2020. We reviewed 35 ELBW infants born between 2017 and 2018 in our hospital, who served as the non-management group. The management group had a significantly lower incidence rate of IVH greater than grade 2 (p = 0.02). Other outcomes showed no significant differences. Dobutamine was prescribed in 8 cases in the management group, and end-systolic wall stress (ESWS) was significantly decreased after Dobutamine administration (p = 0.017). Conclusion: The incidence rate of IVH greater than grade II in ELBW infants decreased after use of customized circulatory management in our study. The strategy of customized circulatory management might be an effective “early target therapy” for hemodynamically significant PDA in high-risk ELBW infants. Inotropic therapy with Dobutamine could be a useful medical choice for improving cardiac function to prevent hemorrhagic complications.